High Dietary Fat Exacerbates Weight Gain and Obesity in Female Liver Fatty Acid Binding Protein Gene-Ablated Mice - Atshaves, Barbara P. (2009)
Since liver fatty acid binding protein (L-FABP) facilitates uptake/oxidation of long-chain fatty acids in cultured transfected cells and primary hepatocytes, loss of L-FABP was expected to exacerbate weight gain and/or obesity in response to high dietary fat. Male and female wild-type (WT) and L-FABP gene-ablated mice, pair-fed a defined isocaloric control or high fat diet for 12 weeks, consumed equal amounts of food by weight and kcal. Male WT mice gained weight faster than their female WT counterparts regardless of diet. L-FABP gene ablation enhanced weight gain more in female than male mice—an effect exacerbated by high fat diet. Dual emission X-ray absorptiometry revealed high-fat fed male and female WT mice gained mostly fat tissue mass (FTM). L-FABP gene ablation increased FTM in female, but not male, mice—an effect also exacerbated by high fat diet. Concomitantly, L-FABP gene ablation decreased serum β-hydroxybutyrate in male and female mice fed the control diet and, even more so, on the high-fat diet. Thus, L-FABP gene ablation decreased fat oxidation and sensitized all mice to weight gain as whole body FTM and LTM—with the most gain observed in FTM of control vs high-fat fed female L-FABP null mice. Taken together, these results indicate loss of L-FABP exacerbates weight gain and/or obesity in response to high dietary fat.